Interactive surveys during online lectures for IT students - Olena S. Holovnia; Natalia O. Shchur; Iryna A. Sverchevska; Yelyzaveta M. Bailiuk; Oleksandra A. Pokotylo (Academy of Cognitive and Natural Sciences, 2023)
The article investigates student response systems (SRS), and how to apply them to facilitate students' engagement and to improve the overall students' experience during online lectures. The authors give an overview of different student response systems (Mentimeter, AhaSlides, Kahoot!, Wooclap, Socrative, Poll Everywhere, and Slido) and make a comparison of their features. The work describes the experience of using the Mentimeter student response system at online lectures in the Operating Systems course for second-year students IT students of Zhytomyr Polytechnic State University (Software Engineering, Computer Science, Computer Engineering, and Cybersecurity specializations). The data is collected using observation, surveys and taking existing data. Data analysis methods include visual analysis (box plots, Q-Q plots, histograms) and statistical analysis (descriptive statistics, Shapiro-Wilk normality test, F-test, Kruskal-Wallis rank sum test). The study provides experimental results showing an increase in the number of students' answers within the lectures. It also highlights IT students' problems and preferences during online lectures. The authors give recommendations on using SRS during online lectures, aimed at improving the lecturer's interaction with the audience.